Programming techniques for economic development : with special reference to Asia and the Far East - United Nations. Economic Commission for Asia and the Far East.; First Group of Experts on Programming Techniques (Bangkok : United Nations Economic Commission for Asia and the Far East, 1960)
The report is to review and sum up the developments in evolving techniques and methods of planning, and to present them in a form that will serve as a guide for official planning bodies, especially those in the ECAFE region, in preparing a comprehensive and logically consistent plan.
"United Nations publication. Sales no.: 60.II.F.3."
Report of the First Group of Experts on Programming Techniques.
Includes bibliographical references: p. 121-130.
osc 12/12/2018
Loans
Keywords: Economic development; Economic policy--Planning; Asia; Far East